Corticosteroid use as adjunct therapy for respiratory syncytial virus infection in adult allogeneic stem cell transplant recipients. Issue 2 (1st April 2016) - Damlaj, M.; Bartoo, G.; Cartin‐Ceba, R.; Gijima, D.; Alkhateeb, H.B.; Merten, J.; Hashmi, S.; Litzow, M.; Gastineau, D.; Hogan, W.; Patnaik, M.M.
Abstract: Background: Respiratory syncytial virus (RSV) infection causes significant morbidity and mortality in allogeneic stem cell transplant (allo‐SCT) recipients. Although ribavirin and immunoglobulins are common components of therapy, the role of adjunct corticosteroids is not established. Objectives: We sought to evaluate corticosteroid utilization in the setting of post‐allo‐SCT RSV infection in our center and assess post‐transplant outcomes including pulmonary function decline. Methods: Patients with a history of RSV infection from 2008 to 2014 seen at our institution were identified. Treatment and outcome data were retrospectively collected. Forced expiratory volume at 1 s (FEV1) and carbon monoxide diffusion capacity (DLCO) were collected pre‐ and post‐RSV infection. Results: During the observation period, RSV was isolated in 53 of 552 patients undergoing allo‐SCT (10%) and 45 had evaluable therapy data. RSV‐related mortality in this cohort was 4/45 (9%). Twenty‐one (47%) were on corticosteroids prior to RSV diagnosis, of whom 11 (24%) had a dose increase post symptom onset. Eight (18%) patients were started on corticosteroids at the time of RSV infection. Corticosteroid therapy at symptom onset was associated with a higher rate of upper respiratory infection (URTI) to lower respiratory infection (LRTI) progression risk ratio (RR) 2.49 (1.21–5.13; P = 0.016), hospital admission RR 2.05 (1.24–3.37; P = 0.005), or intensive care unit admission RR 2.91 (1.89–5.01; P = 0.002). No significant difference was seen with FEV1 and DLCO decline ( P = 0.3 and 0.24, respectively) or mortality ( P = 0.26). Conclusion: Adjunct corticosteroid use in the setting of RSV infection did not improve RSV‐related outcomes including long‐term pulmonary function. Our results do not support the routine use of corticosteroids; however, this finding does need to be verified in a larger cohort of patients.